Parenting goes digital: Performing family, morality, and public identity on Instagram reels - Utami, Setyani; Vera, Nawiroh; Basit, Abdul; Putri, Dhita Widya (PRofesi Humas, 2026)
Background: Parenting practices that were once limited to the domestic sphere are now commonplace in public spaces, largely due to social media. These curated and displayed parenting practices have become part of an effort to construct meaning that requires audience legitimacy to become a representation of ideal meaning. Purpose: This study aims to examine how Yane Ardian shapes the meaning of parenting in her Instagram Reels, the ideal family values she promotes, and how she communicates her self-image as a mother. Methods: This study uses a qualitative method. Thematic and visual coding were employed to deliberately choose 16 Instagram Reels for study. Results: The findings demonstrate that the constructed meaning in parenting practices emphasizes maternal care, character-driven education, child safety, and moral accountability. Parenting is no longer just a part of family life; it may also help shape a person’s identity by teaching them social and cultural values. Reels can help get closer to the audience and achieve moral validity by delivering personal stories that use emotional symbols and supporting visual elements. On the other hand, people prefer content about family life and parenting to social topics. Conclusion: Instagram Reels can become part of a cultural text where ideal parenting practices are represented through compassion, responsibility, and risk. Implications: This research theoretically expands the scope of representation studies by making the phenomenon of “parenting goes digital” an arena for constructing meaning and identity for mothers. Practically, this research contributes to the study of digital communication and public relations by showing how parenting narratives can be used to build emotional closeness with audiences in the digital space.